Mannich Bases: Synthesis, Pharmacological Activity, and Applications: A Review - Raoof , Sura S.; Sadiq, Amaal S. (Iraqi Journal of Science, 2022)
The Mannich reaction is one of the most important types of organic chemistry fundamental reactions. It is a crucial stage in the production of various medicines, natural goods, and industrial chemicals. Chemists' imaginations have always been piqued because of this. In general, the Mannich reactions can be used as part of a tandem reaction sequence to produce complex target molecules in an elegant and often easy manner. The following article examines and summarizes methods for synthesizing Mannich derivatives, in addition to offering a survey of recent advancements in several fields’ applications of the Mannich reaction, such as biological applications, antimicrobial activity, anticancer activity, anti-inflammation and antioxidant activity, antimalarial activity, anti-viral activity, and so on. We also go over how mannich base is used in industry and agriculture.